Prediction of coal seam gas content based on the correlation between gas basic parameters and coal quality indexes - Dai, Linchao; Lei, Hongyan; Cheng, Xiaoyang; Li, Rifu (Frontiers in Energy Research, 2023)
The measurement of gas content in coal seam by means of indirect method involves heavy workload, long period, high cost and complicated operation and a proneness of negative values in the process of measuring gas absorption constant. To address these problems, the gas basic parameters and coal quality indexes of 90 coal samples from 90 coal mines in 13 provinces of China are determined experimentally in this paper. The intrinsic relationship between gas adsorption constant a and atmospheric adsorption capacity Q0-initial velocity index of gas emission Δp, gas adsorption constant b and volatile Vdaf - apparent density ARD is analyzed, and a prediction model of coal seam gas content based on gas basic parameters and coal quality index is established. The results show that the effect of Q0-Δp correlation on a is mainly caused by the change of specific surface area and gas pressure of coal, while the effect of Vdaf-ARD correlation on b is mainly caused by the change of pore volume of coal. By comparing the predicated value from the prediction model of coal seam gas content with the measured value, it is found that the average absolute error rate of predicted value is 8.15%. This method is proven to be effective and feasible in routine gas content predictions, and can provide a reference for coal seam gas content prediction in China.